ANALISA DAMPAK KEPUTUSAN PRESIDEN NOMOR 17 TAHUN 2023 TERHADAP TINGKAT KUNJUNGAN WISATAWAN ASING DI JAWA TIMUR (STUDI KASUS KANTOR IMIGRASI KELAS 1 KHUSUS TPI SURABAYA) - Putra, Diky Aditya; Zahidi, M. Syaprin (Polteknik Imigrasi, 2024)
Indonesia has issued several regulations governing this pandemic, the majority of which regulate population movements both within and outside Indonesia's territory. As time went by, after people began to worry less about the existence of this virus because vaccinations had become evenly distributed and the number of people infected with this virus began to decline significantly, WHO finally declared in May 2023 that the Covid-19 pandemic was officially over. On the basis of the release of this statement, President Joko Widodo a month after the statement was made, in June 2023, issued Decision Number 17 of 2023 which declared the end of the pandemic status. This decision is certainly a breath of fresh air for the economic sector, especially tourism. With the issuance of this decision, it is hoped that foreign tourists will no longer have any doubts about visiting Indonesia. Of course, with this fact, the Indonesian economy, which was previously down, is expected to rise, therefore, it is interesting to examine more deeply the presidential decision. The aspects that can be seen are the background of the decision being taken, as well as the impact it will have. occurred afterwards.